Ionic-Liquid-Based Polyurethane Dispersions for Stabilizing Graphene in Water. (2019) - Gupta, Harshit; Texter, John
ABSTRACT: Aqueous auto-dispersing polyurethane dispersions (PUDs) have recently been reported to form nanoparticulate dispersions at up to 25% by weight. Their incorporation of an ionic-liquid (IL) monomer, 1-hydroxyundecyl-3-methyl imidazolium bromide (HOC11 C1 ImBr) as a chain-terminating group appears to account for their auto-dispersing ability, and these PUD nanoparticles bear similarity to IL-based nanolatexes that have provided thermodynamically stable aqueous dispersions of nanocarbons. We demonstrate that these HOC11 C1 ImBr-based PUDs stabilize aqueous graphene dispersions at 1% by weight graphene in ultrasonicated top-down liquid phase exfoliation. Their formation quantitatively follows an analytical model of exfoliation kinetics of layered materials and a stretched exponential kinetic model. Such dispersions are ideally formulated for making nanocomposites composed of similar or compatible PUDs and other condensation polymers.